Axonemal Growth and Alignment During Paraspermatogenesis in the Marine Gastropod Strombus luhuanus - Shibata, Daisuke; Morita, Masaya; Sato, Yu; Shiba, Kogiku; Kitanobo, Seiya; Yokoya, Ryo; Inaba, Kazuo (Frontiers in Cell and Developmental Biology, 2022)
Parasperm are non-fertilizing sperm that are produced simultaneously with fertile eusperm. They occur in several animal species and show considerable morphological diversity. We investigated the dynamics of axonemes during paraspermatogenesis in the marine snail Strombus luhuanus. Mature parasperm were characterized by two lateral undulating membranes for motility and many globular vesicles. Axonemes were first observed as brush-like structures that extruded from the anterior region. Multiple axonemes longer than the brush then started to extend inside the cytoplasm towards the posterior region. The mass of the axonemes separated into two lateral rows and formed an undulating membrane that drives bidirectional swimming in the mature parasperm. The central pair of axonemes was aligned in the undulating membrane, resulting in cooperative bend propagation. During paraspermatogenesis, centrioles were largely diminished and localized to the anterior region. CEP290, a major component of the transition zone, showed a broad distribution in the anterior area. Axonemes in the posterior region showed a 9 + 0 structure with both outer and inner arm dyneins. These observations provide a structural basis for understanding the physiological functions of parasperm in marine reproductive strategies.